2015
DOI: 10.1111/ijs.12558
|View full text |Cite
|
Sign up to set email alerts
|

A Comparison of Location of Acute Symptomatic vs. ‘Silent’ Small Vessel Lesions

Abstract: BackgroundAcute lacunar ischaemic stroke, white matter hyperintensities, and lacunes are all features of cerebral small vessel disease. It is unclear why some small vessel disease lesions present with acute stroke symptoms, whereas others typically do not.AimTo test if lesion location could be one reason why some small vessel disease lesions present with acute stroke, whereas others accumulate covertly.MethodsWe identified prospectively patients who presented with acute lacunar stroke symptoms with a recent sm… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
42
0
1

Year Published

2015
2015
2022
2022

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 60 publications
(45 citation statements)
references
References 31 publications
2
42
0
1
Order By: Relevance
“…There was no significant right‐left difference in RSSI volumes (Wilcoxon signed rank p  = .16), with spatial prevalence already reported in Valdes Hernandez, Maconick, et al. (2015). RSSI was distributed slightly more widely on the left (Figure 2).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…There was no significant right‐left difference in RSSI volumes (Wilcoxon signed rank p  = .16), with spatial prevalence already reported in Valdes Hernandez, Maconick, et al. (2015). RSSI was distributed slightly more widely on the left (Figure 2).…”
Section: Resultsmentioning
confidence: 99%
“…RSSI was found almost exclusively in the posterior limb of the internal capsule and neighboring white and deep grey matter areas: posterior putamen, globus pallidus, and anterior thalamus; coincident with the region assumed to be crossed by the sensory and motor pathways as published previously (Valdes Hernandez, Maconick, et al., 2015). We also found a balance between the number of patients who had the RSSI in the left and right hemisphere, in agreement with another study (Mead, Lewis, Wardlaw, Dennis, & Warlow, 2000).…”
Section: Discussionmentioning
confidence: 99%
“…Wardlaw's group 43 reported that lacunar infarctions in the vascular centrencephalon were more likely to be symptomatic than small subcortical WMI over the convexity; it is possible that in SPRINT, lower blood diastolic pressures may have prevented hypertensive strokes, while an increase in subcortical WMI may have gone undetected. However, if WMI over the convexity and periventricular WMI are due to other forms of small vessel disease, then different approaches will be needed to prevent them.…”
Section: Insights From Mathematical Modelsmentioning
confidence: 99%
“…One explanation is the locations of lesions. A study using probability mapping shows that lesions presenting with stroke were predominantly located in or near the primary motor and sensory tracts, whereas silent lesions were mostly in the basal ganglia and centrum semiovale away from these main tracts 77. Another explanation could be the levels of vessels where the vascular pathologies happened.…”
Section: Introductionmentioning
confidence: 99%